1984
DOI: 10.1227/00006123-198405000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Trigeminal Artery Associated with Intracranial Arterial Aneurysm

Abstract: Two patients with persistent trigeminal artery associated with a ruptured arterial intracranial aneurysm arising from the ipsilateral internal carotid artery at the level of the posterior communicating artery are presented. One patient underwent successful clipping of the aneurysm. The other patient died on the x-ray table shortly after admission during the performance of emergency carotid angiography. In each patient, the anomalous vessel was considered to be incidental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In different angiographic series, the incidence of primitive trigeminal artery is between 0.06% and 0.6% (mean, 0.23%) (Fields, 1968;Krayenbuhl and Yasargil, 1968). It appears highly probable that if undiagnosed or unreported cases are considered, the real incidence of this anomaly is about 1% (Garza-Mercado and Cavazos, 1984). In this study, the incidence of primitive trigeminal artery was found to be 0.11%.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In different angiographic series, the incidence of primitive trigeminal artery is between 0.06% and 0.6% (mean, 0.23%) (Fields, 1968;Krayenbuhl and Yasargil, 1968). It appears highly probable that if undiagnosed or unreported cases are considered, the real incidence of this anomaly is about 1% (Garza-Mercado and Cavazos, 1984). In this study, the incidence of primitive trigeminal artery was found to be 0.11%.…”
Section: Discussionmentioning
confidence: 51%
“…Among the intracranial vascular anomalies, intracranial aneurysms are most commonly (14%) seen (Sugiyama et al, 1987). T h e majority of the intracranial vascular aneurysms occur on the posterior communicating branch of the internal carotid artery (Garza-Mercado and Cavazos, 1984). Two percent of the cases that are combined with aneurysms have an aneurysm of the primitive trigeminal artery itself (Eggers et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous trigeminal-cavernous fistulas are caused by the rupture of aneurysms, which may be likely formed by the diminished wall resistance of embryological arteries. 6,7 Therapeutic intervention is indicated in most patients, given a prominent venous congestion of the eye, cavernous sinus syndrome with cranial nerve palsies, disturbing pulsatile tinnitus or cardiac problems in case of high shunt volume. In a few early cases, surgical obliteration of the cavernous sinus or ligation of the ICA have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the persistent carotid or vertebral basilar anastomoses are usually incidental findings, case reports of associated intracranial vascular anomalies have been described, including arteriovenous malformations and aneurysms. [10][11][12] To our knowledge, no vascular anomalies have been described with a PIA. In the present case, it is uncertain whether this represents an associated abnormality or an incidental finding.…”
Section: Ig Berman and S Stuckeymentioning
confidence: 99%